1995
DOI: 10.1111/j.1541-0072.1995.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mayoral Power on Urban Fiscal Policy

Abstract: Can mayors of American cities overcome the enormous constraints of environmental forces to exert some control over municipal spending priorities? Despite case study evidence suggesting that mayors can and do influence public policy making, the expectation of this research was that mayoral power in a comparative research design likely would not have a pronounced effect on city spending. Using multiple regression techniques and various socioeconomic, demographic, and political variables, the analysis indeed show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 32 publications
0
46
0
2
Order By: Relevance
“…Liebert, 1974;Lineberry and Fowler, 1967;Lyons, 1978;Morgan and Pelissero, 1980;Morgan and Watson, 1995). For instance, Lineberry and Fowler (1967) found that city taxation and expenditure levels were more responsive to socio-economic and racial cleavages in traditional cities, which they argue was because of the necessity of satisfying the local electorate to maintain office.…”
Section: Local Political Structure and Policy Outcomesmentioning
confidence: 99%
“…Liebert, 1974;Lineberry and Fowler, 1967;Lyons, 1978;Morgan and Pelissero, 1980;Morgan and Watson, 1995). For instance, Lineberry and Fowler (1967) found that city taxation and expenditure levels were more responsive to socio-economic and racial cleavages in traditional cities, which they argue was because of the necessity of satisfying the local electorate to maintain office.…”
Section: Local Political Structure and Policy Outcomesmentioning
confidence: 99%
“…Other studies conclude that reformed municipalities spend more (Sherbenou 1961;Nunn 1996;Cole 1971;French 2004). Others find a null effect (Lyons and Morgan 1977;Dye and Garcia 1978;Morgan and Pelissero 1980;Deno and Mehay 1987;Hayes and Chang 1990;Morgan and Watson 1995). 16 In states that do not officially have county governments, we use the county area, as designated by the Census of Governments.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, scholars of urban politics have focused on the economic, political, and legal constraints facing local policymakers (Gerber and Hopkins 2011;Leigh 2008;Nivola 2002;Peterson 1981Peterson 1995Rae 2003;Self 2003). Due to the multitude of constraints on local governments, most past work has concluded that political factors have little influence on local policy outputs (Craw 2006;Gerber and Hopkins 2011;Morgan and Watson 1995;Peterson 1981;Ruhil 2003;Wolman, Strate, and Melchior 1996). However, there have been no comprehensive studies about whether city policies are actually responsive to the views of their citizens.…”
mentioning
confidence: 99%